2002
DOI: 10.1207/s15327663jcp1202_04
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Evaluation of Low Price Guarantees: The Moderating Role of Reference Price and Store Image

Abstract: This article reports the findings of 2 studies that examined the effects of low price guarantees (LPG) in retail advertisements within the framework of signaling theory. Overall, an LPG in an ad resulted in higher value perceptions and shopping intentions. Findings also suggest that the effect of an LPG is likely to be moderated by other price cues such as reference prices and by the price image of the store. An LPG resulted in higher value perception and shopping intention when reference prices were low or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…Bitner (1992) Environmental Psychology (Holahan 1986;Darley and Gilbert 1985;Stokols and Altman 1987;Russell and Ward 1982) The link between store environmental elements, emotions and patronage Developed the theoretical model for Environmental Psychology to be applied to retail patronage Arnold, Oum and Tigert (1983) Multinominal Logit Choice Behavior Mathematical Model (Gensch and Recker 1979;McFadden 1980;Punj and Staelin 1978) The link between store characteristics, and patronage Store size, price levels, merchandise display, location, service level, and quality merchandise affect patronage Moore and Carpenter (2006) Consumers' use of reference prices (Biswas et al 2002); price as a signal of quality and value (Grewal et al 1998); response to price reductions (Grewal et al 1996) The link between store characteristics and patronage…”
Section: (Table Continues) (Continued)mentioning
confidence: 99%
“…Bitner (1992) Environmental Psychology (Holahan 1986;Darley and Gilbert 1985;Stokols and Altman 1987;Russell and Ward 1982) The link between store environmental elements, emotions and patronage Developed the theoretical model for Environmental Psychology to be applied to retail patronage Arnold, Oum and Tigert (1983) Multinominal Logit Choice Behavior Mathematical Model (Gensch and Recker 1979;McFadden 1980;Punj and Staelin 1978) The link between store characteristics, and patronage Store size, price levels, merchandise display, location, service level, and quality merchandise affect patronage Moore and Carpenter (2006) Consumers' use of reference prices (Biswas et al 2002); price as a signal of quality and value (Grewal et al 1998); response to price reductions (Grewal et al 1996) The link between store characteristics and patronage…”
Section: (Table Continues) (Continued)mentioning
confidence: 99%
“…Low price guarantee signals create increased credibility amongst consumers in that the perception of a false offer shall have an economic cost for the company making it and therefore, shall have a greater influence on the perceived value of the consumer and future buying intentions (Erevelles, Roy & Yip, 2001;Biswas et al, 2002;Dutta & Biswas, 2005;Lurie & Srivastava, 2005;Dutta & Bhomwich, 2009;Hardesty et al, 2012;Janssen & Parakhonyak, 2013). Thus, when the selling companies are faced with the choice of not making any sort of offer regarding low prices or, in the case that they do, selecting the most appropriate, the following hypotheses have been created:…”
Section: Low Price Signallingmentioning
confidence: 99%
“…Signaling theory (Boulding & Kirmani, 1993;Kirmani & Rao, 2000) suggests that consumers perceive both PMG and EDLP pricing policies as signals of sellers' ability to offer low prices. This is because market and consumer-level disciplinary mechanisms (e.g., consumer search, negative word of mouth and failure to repurchase) increase the costs of false signals; only low cost sellers who have the ability to offer low prices can afford to offer them (e.g., Biswas, Pullig, Yagci, & Dean, 2002;Jain & Srivastava, 2000;Kukar-Kinney & Walters, 2003). Consistent with this rationale, researchers have shown that EDLP policies lower a variety of operating costs (Hoch et al, 1994) and advertising expenses (Lattin & Ortmeyer, 1991).…”
Section: The Impact Of Pmg and Edlp On Consumers' Trusting Beliefsmentioning
confidence: 99%